The impact of brand activism on brand image : the mediating role of perceived brand authenticity and the effect of celebrity and non-celebrity endorsements - Bernardino, Patrícia Ribeiro (2022)
Nowadays, consumers expect brands to be more involved in social matters, which has led in recent years to several global brands taking stands on major socio-political issues. Brand Activism is an increasingly popular topic that has become a part of brands’ marketing strategies. Due to the highly controversial nature of social problems, however, there are long-term consequences that need to be evaluated. This study intends to assess the impact that engaging in social activism has on a brand’s image and how authentic consumers perceive brands’ activism efforts to be. First, a pre-survey was used to select in an unbiased way the social cause and celebrity to be represented in the main study. Afterward, a survey was applied in order to expose the respondents to one of the five different stimuli: Male Celebrity Endorsement; Male Non Celebrity Endorsement; Female Celebrity Endorserment; Female Non-Celebrity Endorsemnt; No Endorsement nor Activism. Main findings suggest that Brand Activism positively impacts the Brand Image, and that Perceived Brand Authenticity fully mediates this effect. Furthermore, Celebrity Endorsed Brand Activism has a higher impact on Brand Image than Non-Celebrity Endorsed Brand Activism, while both Endorsement strategies have the same effect on Perceived Brand Authenticity. This study recommends that brands should only take a stand when there is a congruence between the social cause supported and the companies’ values. Further research should investigate other forms of activism and assess whether the same results apply.